Γ‐Glutamyl kinase is involved in selective autophagy of ribosomes in Saccharomyces cerevisiae. Issue 17 (4th August 2016) - Tatehashi, Yuki; Watanabe, Daisuke; Takagi, Hiroshi
Abstract : γ‐Glutamyl kinase (GK; the PRO1 gene product) is a key enzyme in the Saccharomyces cerevisiae proline biosynthesis pathway. Δpro1 cells are more sensitive to various stresses than wild‐type cells, suggesting that GK has an alternative function independent of proline biosynthesis. We show that PRO1 genetically interacts with UBP3, which encodes ubiquitin‐specific protease, and is required for selective autophagy of ribosomes (ribophagy). Interestingly, yeast cells with PRO1 deletion or expressing inactive GK display a defect for ribophagy but not for nonselective autophagy, indicating that GK activity is indispensable for ribophagy. Gene disruption analysis suggests that ribophagy is important for cell survival during nitrogen starvation. Abstract :